Improving methods of power consumption management of urban electric transport - Шацький, Сергій Петрович (Technology audit and production reserves, 2014)
The problem of improving existing methods of controlling power consumption by urban electric transport is considered in the paper. The main objective of the research lies in improving the power-saving by enhancing methods of managing power consumption of urban electric transport using a statistical observation of power consumption in various aspects of converting power into transport work. Using the method of statistical power consumption management allows maintaining the processes at the level, ensuring optimum power consumption for carrying out transport operations based on control cards. The developed technique allows optimizing management processes and reducing operating costs of the electric transport company. The research results can be applied by scientific and pedagogical workers, post-graduate students, students of educational institutions and specialists of transport companies for managing power consumption processes. The proposed principle can effectively solve the problem of power saving.